2008
DOI: 10.1093/fampra/cmn078
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in GPs' task perceptions, self-efficacy, barriers and practices of nutrition education and treatment of overweight

Abstract: The GPs perceived overweight and nutrition education as important and were still favourable towards prevention. However, their potential to give nutrition education or guide in treatment of overweight was not fully utilized because of decreased self-efficacy factors and perceived barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
43
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 17 publications
6
43
1
1
Order By: Relevance
“…The main outcomes of the focus group sessions were that referral to BeweegKuur by a general practitioner (GP) would provide additional motivation for patients, which is consistent with previous research [15]. The patients emphasized the importance of close collaboration between the different health care professionals and their need to feel safe with these professionals.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The main outcomes of the focus group sessions were that referral to BeweegKuur by a general practitioner (GP) would provide additional motivation for patients, which is consistent with previous research [15]. The patients emphasized the importance of close collaboration between the different health care professionals and their need to feel safe with these professionals.…”
Section: Introductionsupporting
confidence: 79%
“…The primary health care setting can be regarded as a good place to start a lifestyle intervention. In the Netherlands, GPs act as the gatekeepers to health care; they see their patients regularly and know their social environment [15]. Most diabetic patients visit their GP or the practice nurse for a check-up every three months, enabling quick selection of eligible patients for BeweegKuur and detection of relapse after inclusion in the programme.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main professions in primary care dealing with obesity is the general practitioner (GP), and previous surveys have shown that the general public considers GPs to be a credible source of information on nutrition [1,2,3,4] and lifestyle advice [5]. Unfortunately only a small fraction of GPs discuss weight loss interventions [6], physical activity (PA) [4,6,7], and nutrition [6] with patients with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Policies to improve PCPs`nutrition guidance practices might in future benefit from a LISREL-model analysis of determinants of these practices to become more effective (45). We designed the research in such a way that we were able to make it a longitudinal study (46)(47)(48), which allows for monitoring variables and the mechanism of action, and for detecting eventual trends. Glanz et al (49) and Kushner (50) also identified barriers, and Levine et al (10) and Orleans et al (12) carried out US national surveys of PCPs`attitudes and practices to define strategies for enhancing the use of clinical nutrition and health promotion in medical practice.…”
mentioning
confidence: 99%